Use of epoxy asphalt as surfacing and tack coat material for roadway pavements. (30th July 2020) - Apostolidis, Panos; Liu, Xueyan; Erkens, Sandra; Scarpas, Athanasios
Highlights: Epoxy asphalt mixes have higher tensile strength than conventional asphalt mixes. The four-point bending tests indicate that a high modulus material, as the epoxy asphalt, can eﬀectively reduce deflections of specimen beams and improve their fatigue resistance. Epoxy-type tack coat improves significantly the bonding strength between two asphaltic layers. Two-layer monolithic pavements with epoxy asphalt could mitigate bonding defects of surfacing layers of enhanced strength, modulus and fatigue resistance. Abstract: This work presents an experimental program developed to evaluate the effect of epoxy-asphalt binder, used as replacement of bitumen, on the durability and fatigue life of an asphalt concrete mix. The use of epoxy-type binder as tack coat has been explored as well and thus experiments have been conducted to quantify the effect of epoxy tack coat on the interface strength of two-layer asphalt samples. Results indicated that the epoxy asphalt mixes had higher tensile strength than control mixes, and the increase of strength was noticed with increasing proportionally the amount of epoxy in bitumen. Additionally, the four-point bending tests indicate that a high modulus material, as the epoxy modified asphalt, can effectively reduce deflections of specimen beams and improve the fatigue resistance of mixes designed for surfacing roadway applications. On the basis of interlayer tests, the use of epoxy asphalt binder as tack coat improved the bonding strength between the two layers offering monolithic performance characteristics on high modulus roadway pavements. Overall, the current study concludes that a two-layer monolithic pavement system with epoxy asphalt could mitigate bonding defects, such as debonding, slippage and fatigue cracking propagated from bottom to up, of a surfacing (top) pavement layer of enhanced strength, modulus and fatigue resistance.